Comparative Analysis of Non Linear Estimation Schemes used for Undersea Sonar Applications - JAWAHAR A; VISHNU CHAKRAVARTHI CH (Innovare Journal of Engineering and Technology, 2016)
Â Â Â The performance evaluation of various passive underwater target tracking algorithms like Pseudo Linear Estimator, Maximum Likelihood Estimator, Modified Gain Bearings-only Extended Kalman Filter, Unscented Kalman Filter, Parameterized Modified Gain Bearings-only Extended Kalman Filter and Particle Filter coupled with Modified Gain Bearings-only Extended Kalman Filter using bearings-only measurements is carried out with various scenarios in Monte Carlo Simulation. The performance of Parameterized Modified Gain Bearings-only Extended Kalman Filter is found to be better than all estimates.